2022
DOI: 10.11591/ijere.v11i1.22030
|View full text |Cite
|
Sign up to set email alerts
|

Higher order thinking skills, school-based assessment and students’ mathematics achievement: Understanding teachers’ thoughts

Abstract: <span>The purpose of this study was to investigate the effect of incorporating higher order thinking skills (HOTS) in a school-based assessment (SBA) on mathematics achievement among students. A mixed-method case study design was used to assess a sample size of 158 students and three mathematics teachers. The students’ proficiency in mathematics was determined by using the standard based curriculum for secondary schools (</span><em><span>kurikulum standard sekolah menengah/KSSM</span… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Furthermore, teachers are expected to be able to provide HOTS-focused learning [59]. Research conducted in Malaysia showed that it is essential to incorporate HOTS in the classroom learning so that students are inclined to think critically and creatively in everyday life [37]. The results of this study also found that teachers have not been able to compile an assessment at the creating cognitive level.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, teachers are expected to be able to provide HOTS-focused learning [59]. Research conducted in Malaysia showed that it is essential to incorporate HOTS in the classroom learning so that students are inclined to think critically and creatively in everyday life [37]. The results of this study also found that teachers have not been able to compile an assessment at the creating cognitive level.…”
Section: Discussionmentioning
confidence: 78%
“…Assessment is defined as a practice of collecting, studying, and using information related to student learning outcomes in a systematic, comprehensive, and consistent manner to improve student learning and development [37]. Teacher teaching and assessment activities mainly focus on low cognitive levels induced by teacher knowledge and lack of understanding of the alignment between curriculum, teaching, and assessment practices in the Netherlands [38].…”
mentioning
confidence: 99%
“…Hord stated that the PLC practically is a group of motivated or enthusiastic individuals with a vision of learning to support the goal, particularly the development of teachers to have a better understanding of the design and organization of learning activities, in order to cultivate students' higher-order thinking skills by using school-based assessment. This kind of activity management will affect the learning achievement of students [24].…”
Section: Resultsmentioning
confidence: 99%
“…Learning media in the form of illustrations or whatever the name is, can help students to stimulate reasoning. Provide clarity on concepts that are too abstract and can minimize misconceptions [57]. As a tool, learning media has been proven to contribute to mastering the concept of a study topic [58].…”
Section: Icmscementioning
confidence: 99%